Concurrent gut transcriptome and microbiota profiling following chronic ethanol consumption in nonhuman primates. (4th July 2018) - Barr, Tasha; Sureshchandra, Suhas; Ruegger, Paul; Zhang, Jingfei; Ma, Wenxiu; Borneman, James; Grant, Kathleen; Messaoudi, Ilhem
ABSTRACT: Alcohol use disorder (AUD) results in increased intestinal permeability, nutrient malabsorption, and increased risk of colorectal cancer (CRC). Our understanding of the mechanisms underlying these morbidities remains limited because studies to date have relied almost exclusively on short-term heavy/binge drinking rodent models and colonic biopsies/fecal samples collected from AUD subjects with alcoholic liver disease (ALD). Consequently, the dose- and site-dependent impact of chronic alcohol consumption in the absence of overt liver disease remains poorly understood. In this study, we addressed this knowledge gap using a nonhuman primate model of voluntary ethanol self-administration where rhesus macaques consume varying amounts of 4% ethanol in water for 12 months. Specifically, we performed RNA-Seq and 16S rRNA gene sequencing on duodenum, jejunum, ileum, and colon biopsies collected from 4 controls and 8 ethanol-consuming male macaques. Our analysis revealed that chronic ethanol consumption leads to changes in the expression of genes involved in protein trafficking, metabolism, inflammation, and CRC development. Additionally, we observed differences in the relative abundance of putatively beneficial bacteria as well as those associated with inflammation and CRC. Given that the animals studied in this manuscript did not exhibit signs of ALD or CRC, our data suggest that alterations in gene expression and bacterial communities precede clinical disease and could serve as biomarkers as well as facilitate future studies aimed at developing interventions to restore gut homeostasis.